DataSheet_1_Nutrient composition (Si:N) as driver of plankton communities during artificial upwelling.pdf - Silvan Urs Goldenberg (14173797); Jan Taucher (2951682); Mar Fernández-Méndez (471598); Andrea Ludwig (2951688); Javier Arístegui (187385); Moritz Baumann (11610901); Joaquin Ortiz (11610910); Annegret Stuhr (3366170); Ulf Riebesell (172338) (2023)
Artificial upwelling brings nutrient-rich deep water to the sun-lit surface to boost fisheries or carbon sequestration. Deep water sources under consideration range widely in inorganic silicon (Si) relative to nitrogen (N). Yet, little is known about how such differences in nutrient composition may influence the effectiveness of the fertilization. Si is essential primarily for diatoms that may increase food web and export efficiency via their large size and ballasting mineral shells, respectively. With a month-long mesocosm study in the subtropical North Atlantic, we tested the biological response to artificial upwelling with varying Si:N ratios (0.07-1.33). Community biomass increased 10-fold across all mesocosms, indicating that basic bloom dynamics were upheld despite the wide range in nutrient composition. Key properties of these blooms, however, were influenced by Si. Photosynthetic capacity and nutrient-use efficiency doubled from Si-poor to Si-rich upwelling, leading to C:N ratios as high as 17, well beyond Redfield. Si-rich upwelling also resulted in 6-fold higher diatom abundance and mineralized Si and a corresponding shift from smaller towards larger phytoplankton. The pronounced change in both plankton quantity (biomass) and quality (C:N ratio, size and mineral ballast) for trophic transfer and export underlines the pivotal role of Si in shaping the response of oligotrophic regions to upwelled nutrients. Our findings indicate a benefit of active Si management during artificial upwelling with the potential to optimize fisheries production and CO 2 removal.